Early ultraviolet/optical emission of the type Ib SN 2008D - Bersten, Melina Cecilia (2013)
We propose an alternative explanation for the post-breakout emission of SN 2008D associated with the X-ray transient 080109. Observations of this object show a very small contrast of 0.35 dex between the light-curve minimum occurring soon after the breakout, and the main luminosity peak which is due to radioactive heating of the ejecta. Hydrodynamical models show that the cooling of a shocked Wolf-Rayet star leads to a much greater difference (≳ 0.9 dex). Our proposed scenario is that of a jet produced during the explosion which deposits 56Ni-rich material in the outer layers of the ejecta. The presence of high-velocity radioactive material allows us to reproduce the complete luminosity evolution of the object. Without outer 56Ni it could be possible to reproduce the early emission purely from cooling of the shocked envelope by assuming a larger progenitor than a Wolf-Rayet star, but that would require an initial density structure significantly different from what is predicted by stellar evolution models. Analytic models of the cooling phase have been proposed reproduce the early emission of SN 2008D with an extended progenitor. However, we found that the models are valid only until 1.5 days after the explosion where only two data of SN 2008D are available. We also discuss the possibility of the interaction of the ejecta with a binary companion, based on published analytic expressions. However, the binary separation required to fit the early emission should be ≲ 3 R ⊙, which is too small for a system containing two massive stars.